2019
DOI: 10.13045/jar.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

A Facial Chuna Manual Therapy for Peripheral Facial Nerve Palsy

Abstract: The purpose of this study was to investigate useful manual therapy techniques for peripheral facial nerve palsy and to propose guidelines to be applied for current manual therapy techniques. Several databases were searched to find manual therapies for facial palsy. These therapies included cervical, and temporomandibular joint chuna manual therapy, proprioceptive neuromuscular facilitation, neuromuscular re-education, facial exercise, and mime therapy. Both cervical, and temporomandibular joint chuna manual th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that contracture decreases the number and size of muscle cells, and increases the connective tissue, and fat mass on the paralyzed side as observed microscopically [18]. Symptoms of contracture include a feeling of rigidity of the facial muscles, a narrowing of the eyelids, and a deepening of the nasolabial folds [12]. Crocodile tears syndrome (where the masticatory muscles and lacrimal glands are connected) was named after the belief that crocodiles shed tears when eating [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that contracture decreases the number and size of muscle cells, and increases the connective tissue, and fat mass on the paralyzed side as observed microscopically [18]. Symptoms of contracture include a feeling of rigidity of the facial muscles, a narrowing of the eyelids, and a deepening of the nasolabial folds [12]. Crocodile tears syndrome (where the masticatory muscles and lacrimal glands are connected) was named after the belief that crocodiles shed tears when eating [7].…”
Section: Discussionmentioning
confidence: 99%
“…Synkinesis is one of the symptoms among the sequelae of facial palsy which causes the patient to become uncomfortable. This is a symptom in which unintended facial muscles move together when a specific facial muscle is moved [12]. The most common symptom is a combination of mouth and eye movements, such as closing the eyes when smiling or raising the corners of the mouth when blinking eyes [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the trigeminal nerve f ibers receive proprioceptive sensations from the facial muscles and simultaneously deliver neural information to the central nervous system [12,13]. This can lead to nerve re-education and muscle recovery, by providing effective neurofeedback for the paralyzed facial muscle movement by assisting the origin and resisting the insertion region of the facial muscle [14,15].…”
Section: Discussionmentioning
confidence: 99%